Human Resource Valuation: Perspectives on External Financial Reporting in terms of Decision Usefulness - Nodee, Mahpara; Karim, Ziaul (Asian Accounting and Auditing Advancement, 2019)
Globalization has made its way into the business world and it demands true and fair financial information to be reported in the financial statements of companies around the world. To ensure that, businesses should prepare their statements in such a way that embodies the financial and physical assets along with human assets. The benefits generated if human resources are expressed numerically are manifold. Despite that, questions are raised regarding the applicability of human resource accounting models. This is an exploratory study where the decision usefulness of human resource accounting information presented in external reports is assessed. In this study, existing literature on the widely used qualitative human resource valuation models is carefully examined against the prescribed qualitative characteristics of external financial accounting information. Whether the models comply, and if not, the extent of non-compliance is analyzed. In addition, the loopholes in the valuation models that form the basis of such non-compliance are identified. This ultimately represents the scope for a further research study. Finally, this study acknowledges that reported information can only be made decision-useful for external parties if the information follows the combination of qualitative criteria established by major global bodies. It is then recommended that future models should be aligned considering such qualities so as to produce fruitful external information for decision making.